2017
DOI: 10.1016/j.amjcard.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mortality and Nonfatal Cardiovascular Events in Adults With Atrial Fibrillation With Versus Without Levothyroxine Treatment

Abstract: Levothyroxine has been suggested to be cardiotoxic but previous studies on the risk of cardiovascular events associated with levothyroxine treatment have been inconclusive. We aimed to study the association between levothyroxine treatment and all-cause mortality as well as cardiovascular events. Study population included all adults (n=12,283) ≥45 years diagnosed with atrial fibrillation (AF) at 75 primary care centers in Sweden 2001–2007, with (n=1,189; 283 men and 906 women) or without (n=11,094) levothyroxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…These results suggest that physiological doses of T3 in low TH conditions do not promote arrhythmias, a finding confirmed recently by the TRUST trial (28). Wandell et al also showed that women diagnosed with AF who were being treated with T4 had a decreased risk of mortality (29). Previous studies reported that mutations in Kcna5 could enhance AF susceptibility (30).…”
Section: Changes In Infarct Parameters and Left Atrial Fibrosismentioning
confidence: 58%
“…These results suggest that physiological doses of T3 in low TH conditions do not promote arrhythmias, a finding confirmed recently by the TRUST trial (28). Wandell et al also showed that women diagnosed with AF who were being treated with T4 had a decreased risk of mortality (29). Previous studies reported that mutations in Kcna5 could enhance AF susceptibility (30).…”
Section: Changes In Infarct Parameters and Left Atrial Fibrosismentioning
confidence: 58%
“…A study from the Cleveland Clinic Preventative Cardiology Clinic showed that untreated patients with TSH levels greater than 6.1 µIU/ml had higher all-cause mortality 36 . Another study on adults with atrial fibrillation (AF) with or without levothyroxine treatment showed that levothyroxine treatment decreased the mortality risk in women with AF and reported that the treatment seemed to be safe 37 . According to our study, we found that severe SHT was associated with obvious myocardial injuries by T1 mapping CMR and should be treated.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, we found CHF positively associated with prevalent dementia but negatively with incident dementia [26]. Furthermore, being registered with a diagnosis of hypothyroidism has been shown to be associated with a lower mortality risk compared with only a levothyroxine prescription among both men and women with AF [20].…”
Section: Discussionmentioning
confidence: 92%
“…The relationship between hypothyroidism, levothyroxine, and survival has been elucidated in earlier research, where hypothyroidism and levothyroxine treatment was associated with a lower cardiovascular risk and mortality [20], even if the potential mechanism explaining the association between levothyroxine treatment and mortality is unknown. Women have a higher prevalence of hypothyroidism and are more commonly treated with levothyroxine [21].…”
Section: Introductionmentioning
confidence: 99%